Faktor yang Berhubungan dengan Pemanfaatan Pelayanan Imunisasi Dasar di Posyandu Terkini 1 Desa Mario - Naya Dwiyanti; Mardhatillah Mardhatillah; Devy Febrianti (Pusat riset dan Inovasi Nasional, 2025)
Basic immunization is one of the main pillars in the effort to control infectious diseases, which is important for the health of children from an early age. In order to achieve optimal health, immunization helps prevent diseases such as diphtheria, tetanus, whooping cough, polio, and measles that can cause serious complications or even death. The immunization program implemented at Posyandu Terkini 1 in Mario Village has a positive impact on public health, with an immunization coverage rate showing 97.90% in the South Sulawesi region. This study focuses on factors that influence the utilization of basic immunization at Posyandu Terkini 1 in Mario Village. In a quantitative research design with a cross-sectional approach, researchers involved the entire population consisting of 89 infants and toddlers in Mario Village through a total sampling method. Using the Chi Square test, this study identified factors related to the utilization of immunization services, namely maternal knowledge, maternal attitudes, family support, and support from health workers. The results showed that these factors significantly influenced the utilization of basic immunization, while access to immunization services did not show a significant relationship. This research makes an important contribution to the development of public health policies, particularly in increasing community participation in immunization programs. With a more integrated approach, particularly in educating the community about the benefits of immunization and the importance of support from families and health workers, it is hoped that immunization coverage in villages will be broader and more equitable. These findings will be published in the Jurnal Kesehatan (Health Journal) to provide further insights for relevant stakeholders in improving the quality of immunization services. Furthermore, this study also emphasizes the importance of the active role of health workers in educating parents, especially mothers, about the benefits of immunization and the vaccine schedule.